TINDAKAN PERATAAN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Astuti Yuli Setyani; Rikha Liffa (Fakultas Bisnis UKDW, 2012)
This study aimed to examine the effect of public ownership structure, industry type, firm size, profitability and financial risks affecting the income smoothing. Sample used in this study were 107 companies included in the manufacturing industry, financial institutions and real estate, and properties listed on Indonesia Stock Exchange in 2005-2009. The data analysis technique that used is logistic regression. The results obtained from this study showed that the profitability and financial risk affects the income smoothing, while the structure of public ownership, type of industry and firm size has no effect.Keywords: profitability, financial risk, income smoothing